Characterization of a Pentacyclic Triterpene Acetyltransferase Involved in the Biosynthesis of Taraxasterol and ψ-Taraxasterol Acetates in Lettuce - Choi, Han Suk; Han, Jung Yeon; Cheong, Eun Ju; Choi, Yong Eui (Frontiers in Plant Science, 2022)
Triterpenoids exist in a free state and/or in conjugated states, such as triterpene glycosides (saponins) or triterpene esters. There is no information on the enzyme participating in the production of triterpene esters from free triterpenes. Lettuce (Lactuca sativa) contains various pentacyclic triterpene acetates (taraxasterol acetates, ψ-taraxasterol acetates, taraxerol acetates, lupeol acetates, α-amyrin acetates, β-amyrin acetates, and germanicol acetate). In this study, we report a a novel triterpene acetyltransferase (LsTAT1) in lettuce involved in the biosynthesis of pentacyclic triterpene acetates from free triterpenes. The deduced amino acid sequences of LsTAT1 showed a phylogenetic relationship (43% identity) with those of sterol O-acyltransferase (AtSAT1) of Arabidopsis thaliana and had catalytic amino acid residues (Asn and His) that are typically conserved in membrane-bound O-acyltransferase (MBOAT) family proteins. An analysis of LsTAT1 enzyme activity in a cell-free system revealed that the enzyme exhibited activity for the acetylation of taraxasterol, ψ-taraxasterol, β-amyrin, α-amyrin, lupeol, and taraxerol using acetyl-CoA as an acyl donor but no activity for triterpene acylation using a fatty acyl donor. Lettuce oxidosqualene cyclase (LsOSC1) is a triterpene synthase that produces ψ-taraxasterol, taraxasterol, β-amyrin and α-amyrin. The ectopic expression of both the LsOSC1 and LsTAT1 genes in yeast and tobacco could produce taraxasterol acetate, ψ-taraxasterol acetate, β-amyrin acetate, and α-amyrin acetate. However, expression of the LsTAT1 gene in tobacco was unable to induce the conversion of intrinsic sterols (campesterol, stigmasterol, and β-sitosterol) to sterol acetates. The results demonstrate that the LsTAT1 enzyme is a new class of acetyltransferase belong to the MBOAT family that have a particular role in the acetylation of pentacyclic triterpenes and are thus functionally different from sterol acyltransferase conjugating fatty acyl esters.